PENGARUH TINGKAT PENDIDIKAN, STATUS KETENAGAKERJAAN, JUMLAH ANGGOTA KELUARGA, DAN ALASAN MENIKAH TERHADAP USIA KAWIN PERTAMA PEREMPUAN DI KOTA DENPASAR - Haryanti, Angelita Megah Dwi; Yasa, Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The purpose of this study was to analyze the simultaneous influence of education level, employment status, number of family members, and reasons for marriage on the age of first marriage of women in Denpasar City and to analyze the partial effects of education level, employment status, number of family members, and reasons for marriage on the age of first marriage of women in Denpasar City. The number of samples taken was 99 PUS wives. Methods of data collection using structured interviews and in-depth interviews. The data analysis technique used multiple linear regression analysis. The results show that 1) Simultaneously the level of education, employment status, number of family members, and reasons for marriage have a significant effect on the age of first marriage of women in Denpasar City. 2) Partially the level of education has a positive and significant effect on the age of first marriage of women in Denpasar City. 3) Partially the number of family members has a negative and significant effect on the age of first marriage of women in Denpasar City. 4) Female respondents who are working have a higher age of first marriage than female respondents who are not working, but the difference is not significant. 5) Respondents of women who married for reasons of premarital pregnancy have a lower age of first marriage than female respondents who were married not because of premarital pregnancy and the difference is significant . K eyword: age of first marriage, level of education, employment status, number of family members, reasons for marriage Classification JEL: J13, J14